Adobe illustrator y su incidencia en el aprendizaje a los estudiantes del tercer año debachillerato en el área informática de la Unidad Educativa Emigdio Esparza Moreno, Cantón Babahoyo, Provincia de los Ríos, del periodo lectivo 2017 - Camposano Vargas, Laura Carolina (2017)
This research project has been carried out in the Educational Unit Emigdio Esparza Moreno, where they will explain the incidence of adobe learning Illustrator, with this resource students can create their knowledge the application of strategies and how to create vectors as they are demonstrative examples made In the mentioned program will achieve that the learning is significant for the knowledge and increase of manipulation of certain vectorial graphic tools for an improvement and attractive, this project is feasible because it has the technical knowledge and the capacity to carry it out without discussion , In this research project it was considered necessary to resort to the resources corresponding to random sampling, since the quality of population involved was taken as a sample due to not exceeding the limit. The study of research instruments such as observation, interview and survey by means of a questionnaire of questions whose results admitted to be the proposal